The Onset of Tacrolimus Biosynthesis in Streptomyces tsukubaensis Is Dependent on the Intracellular Redox Status - Pires, Sílvia D. S. (Antibiotics (Basel), 2020)
The oxidative stress response is a key mechanism that microorganisms have to adapt to changeling environmental conditions. Adaptation is achieved by a fine-tuned molecular response that extends its influence to primary and secondary metabolism. In the past, the role of the intracellular redox status in the biosynthesis of tacrolimus in Streptomyces tsukubaensis has been briefly acknowledged. Here, we investigate the impact of the oxidative stress response on tacrolimus biosynthesis in S. tsukubaensis. Physiological characterization of S. tsukubaensis showed that the onset of tacrolimus biosynthesis coincided with the induction of catalase activity. In addition, tacrolimus displays antioxidant properties and thus a controlled redox environment would be beneficial for its biosynthesis. In addition, S. tsukubaensis ∆ahpC strain, a strain defective in the H(2)O(2)-scavenging enzyme AhpC, showed increased production of tacrolimus. Proteomic and transcriptomic studies revealed that the tacrolimus over-production phenotype was correlated with a metabolic rewiring leading to increased availability of tacrolimus biosynthetic precursors. Altogether, our results suggest that the carbon source, mainly used for cell growth, can trigger the production of tacrolimus by modulating the oxidative metabolism to favour a low oxidizing intracellular environment and redirecting the metabolic flux towards the increase availability of biosynthetic precursors.